Engineering Design of a Hybrid Groundwater Treatment System in Suka Damai Village, Muara Badak Subdistrict, Kutai Kartanegara Regency - Ansahar Ansahar; Felix Alan Shinata; Syah Elgar Gibrany; Wira Kusuma; Daffa Arya Saputra; Febrian Nanendra (Magister Teknik Mesin Universitas Pancasila, 2026)
Groundwater serves as the primary source of clean water for residents of Suka Damai Village, Muara Badak Subdistrict, Kutai Kartanegara Regency. However, laboratory analyses reveal severe microbiological and physicochemical contamination in both shallow dug wells and deep boreholes, exceeding the standards set by the Indonesian Ministry of Health Regulation No. 2 of 2023. This study aims to design a hybrid groundwater treatment system based on empirical laboratory data to produce safe drinking water. Water samples were collected from two strategic locations—a deep borehole and a shallow dug well—and analyzed at the Environmental Laboratory of DLHK Kutai Kartanegara. Results showed that raw water exhibits total coliform levels up to 6,488 MPN/100 mL, E. coli at 259 MPN/100 mL, total dissolved solids (TDS) of 704 mg/L (exceeding the 300 mg/L standard), turbidity of 47.6 NTU, and offensive odor. Based on these findings, a three-stage hybrid system is recommended: (1) aeration using an aeration tower, (2) multistage filtration (zeolite sand, manganese media, granular activated carbon), and (3) ultraviolet (UV) disinfection—deliberately avoiding chlorine to prevent the formation of carcinogenic disinfection by-products (DBPs), such as trihalomethanes (THMs). System sustainability is ensured through a governance model managed by the Village-Owned Enterprise (BUMDes) and supported by household willingness to pay (WTP) of IDR 50,000–150,000 per month. This research demonstrates that contaminated groundwater can be transformed into safe drinking water through an integrated approach combining appropriate technology, social engagement, and renewable energy.